2018
DOI: 10.21303/2504-5695.2018.00789
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Weather Conditions of the Vegetational Period for the Formation of the Nutrient Value of Cauliflower

Abstract: The influence of weather conditions of the vegetation period on the formation of the food value of cauliflower was studied. Weather conditions of the vegetation period influenced the formation of the food value of cauliflower. More dry substances 8,4-15,5 % depending on a hybrid accumulated in a drying and hot 2017 year. The content of dry substances in heads of early ripen hybrids of cauliflower during 2015-2017 was within 6,1-10,9 % depending on a hybrid. In 2016 and 2017 there accumulated more of them. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Additionally, in summer growing conditions, the process of accumulation of ascorbic acid has a wavelike character. This can be explained by the fact that, firstly, fluctuations in environmental factors have a significant impact on the synthesis of vitamin C [42]. In addition, for this analysis, the titration method was used, which was chosen on the basis of, comparison of titration methods and spectrophotometry carried out by other researchers [43], showed that there is not much difference between the two methods.…”
Section: Objectivementioning
confidence: 99%
“…Additionally, in summer growing conditions, the process of accumulation of ascorbic acid has a wavelike character. This can be explained by the fact that, firstly, fluctuations in environmental factors have a significant impact on the synthesis of vitamin C [42]. In addition, for this analysis, the titration method was used, which was chosen on the basis of, comparison of titration methods and spectrophotometry carried out by other researchers [43], showed that there is not much difference between the two methods.…”
Section: Objectivementioning
confidence: 99%